1999
DOI: 10.1161/01.str.30.5.1144
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion- and Perfusion-Weighted Magnetic Resonance Imaging in Deep Cerebral Venous Thrombosis

Abstract: Background-Diffusion-weighted (DWI) and perfusion-weighted (PI) MRI are highly sensitive techniques for early diagnosis of arterial infarction, but little data on venous cerebral ischemia are available. We describe a case in which DWI, PI, and fast T2-weighted sequences were performed in the acute phase of deep cerebral venous thrombosis (CVT). Case Description-An 11-year-old girl with Crohn's disease developed deep CVT in which extensive edema was shown in the deep gray matter on T2-weighted sequence images. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
3
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(64 citation statements)
references
References 13 publications
1
57
3
3
Order By: Relevance
“…10 Alternatively, previous experimental studies showed that retrograde venous pressure might counteract capillary perfusion pressure to decrease cerebral blood flow, and thus cause arterial ischemia resulting in cellular or cytotoxic edema. 12,21 Previous experimental and clinical diffusion-weight imaging studies of cerebral venous thrombosis have shown that ADC value was decreased, 12,22,23 normal, 23 increased, 24 or heterogeneous. 25,26 The ADC values decreased by 56% at 30 minutes after experimental cerebral venous thrombosis, and secondary increases in ADC subsequently developed in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…10 Alternatively, previous experimental studies showed that retrograde venous pressure might counteract capillary perfusion pressure to decrease cerebral blood flow, and thus cause arterial ischemia resulting in cellular or cytotoxic edema. 12,21 Previous experimental and clinical diffusion-weight imaging studies of cerebral venous thrombosis have shown that ADC value was decreased, 12,22,23 normal, 23 increased, 24 or heterogeneous. 25,26 The ADC values decreased by 56% at 30 minutes after experimental cerebral venous thrombosis, and secondary increases in ADC subsequently developed in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…This may include DWI abnormalities consistent with acute infarction, but the degree of DWI findings may be reduced in venous infarction compared with arterial infarction ( Figure 7). 124 An altered enhancement pattern suggestive of collateral flow or of venous congestion may be seen. There are some characteristic patterns of brain parenchymal changes that distinguish CVT from other entities.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Normally, the early veins begin to opacify at 4 to 5 seconds after injection of contrast material into the carotid artery, and the complete cerebral venous system is opacified in 7 to 8 seconds. 74,91,124,152 If cerebral veins or dural sinuses are not visualized in the normal sequences of cerebral angiography, the possibility of acute thrombosis is suspected. This finding accounts for the observed delayed cerebral perfusion seen with perfusionweighted MRI with prolonged transit time.…”
Section: Cerebral Angiographymentioning
confidence: 99%
“…Достоверно дифференциро-вать вазогенный отёк от цитотоксического можно с помощью МР-режимов DWI и ADC (apparent diffusion coefficient -истинный коэффициент диффузии) картирования. Вазогенный отёк ха-рактеризуется гипо-или изоинтенсивными оча-гами на DWI [41] и повышением интенсивности сигнала при ADC-картировании [42]. Проявле-ния вазогенного отёка раньше, чем цитотокси-ческого, причисляют к особенностям венозного инфаркта [1,41].…”
Section: *шагом паттерна (+или -) принято счи-тать увеличение или умеunclassified